The Potential of Leukocyte Ratio to Differ Pediatric Tuberculosis from Bronchopneumonia - Benita, Krist Nathania; Wulandari, Asih Retno; Purwaningtyas, Retno (Asian Journal of Health Research, 2024)
Introduction: Differentiating between TB and pneumonia is crucial to avoid treatment delays. Delayed diagnosis can result in reduced patient survival rates, increased treatment expenses and prolonged treatment durations. Several leukocyte ratios such as Neutrophil-lymphocyte ratio (NLR), lymphocyte-monocyte ratio (LMR), platelet-lymphocyte ratio (PLR), monocyte-lymphocyte ratio (MLR) will be compared to confirm whether it can be used to distinguished pulmonary tuberculosis from community-acquired pneumonia. Material and Methods: Retrospective study of 100 children aged 1-12 years who were treated at RSUD Dr. Haryoto Lumajang, period 1 January 2019 – 1 January 2023. Data on age, gender, diagnosis and laboratory results were obtained from medical records. Results: Of the 100 children included 50 had TB disease and 50 had pneumonia. The mean of neutrophil counts was significantly higher in the control group compared to the case group. NLR and MLR ratio were statistically significant. NLR were both statistically significant in both <5 years old and >5 years old, but MLR were not significantly different in both age groups. A significant but weak positive correlation was found between tuberculosis (case) group, pneumonia (control) group, and age of children (r=0.132; p=0.048). Younger children (less than 5 years old) had 0.571-fold odds for tuberculosis infection compared to the older children. Conclusion: NLR hold promise as readily accessible diagnostic biomarkers for distinguishing children with TB disease from those with pneumonia.